Nationwide survey of radiation therapy in Japan for lung cancer complicated with interstitial lung disease. (4th May 2020) - Hagiwara, Yasuhito; Nakayama, Yuko; Kudo, Shigehiro; Hayakawa, Toyokazu; Nakamura, Naoki; Kitamoto, Yoshizumi; Takahashi, Shigeo; Tsujino, Kayoko; Kubo, Nobuteru; Tamaki, Yukihisa; Nagata, Yasushi; ,
Abstract: The purpose of this study was to clarify the opinions of radiation oncologists in Japan regarding treatment for lung cancer complicated with interstitial lung disease (ILD) by a questionnaire survey, and the risk of acute exacerbation (AE) after radiotherapy. Questionnaires were sent to all of the facilities in which radiation therapy is performed for lung cancer in Japan by using the mailing list of the Japanese Society for Radiation Oncology (JASTRO). The questionnaire survey was conducted to clarify who judges the existence of ILD, the indications for radiation therapy in cases of ILD-combined lung cancer, and the ratio of ILD-combined lung cancer in lung cancer patients treated with radiation therapy. Patients with ILD-combined lung cancer who received radiotherapy during the period from April 2014 to March 2015 were retrospectively analysed. Any cases of AE without any other obvious cause were included. ILD confirmation was performed by central radiologists using computed tomography images. A total of 47 facilities responded to the questionnaire. Radiation therapy was an option in cases of ILD-combined lung cancer in 39 (83%) of the facilities. The indication for radiation therapy was based on image findings in 35 (90%) of the 39 facilities in which radiation therapy was acceptable or was a choice in some cases of ILD. The final indication was based on the opinion of the pulmonologist in 29 (74%) of those 39 facilities. In fiscal year 2014, a total of 2128 patients in 38 facilities received chest irradiation. Seventy-eight (3.7%) of those 2128 patients had ILD-combined lung cancer. Sixty-seven patients were included in patient analysis. AE occurred in 5 patients (7.5%), and one of those 5 patients (20.0%) died from radiation-induced AE. The median period from radiotherapy to AE was 4 months (range, 2–7 months). The following four independent risk factors for AE were identified in univariate analysis: non-advanced age (<75 years), increased C-reactive protein level (≥0.3 mg/dl), adjuvant chemotherapy and ≥ Grade 2 radiation pneumonitis. Radiotherapy was an option for lung cancer even in cases with ILD in 83% (39/47) of the facilities in Japan. Seventy-eight (3.7%) of 2128 patients who received radiation therapy for lung cancer had ILD. Radiotherapy for ILD-combined lung cancer may induce AE at a substantial rate and AE can be life-threatening. Minimizing the risk of radiation pneumonitis might enable the risk of AE to be reduced.